Copper residue ozone catalyst, preparation method and application thereof
Patent Information
- Application Number
- CN202411068297.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-08-06
AI Technical Summary
上述专利利用双氧水和EDTA,用以提高电解效率,但其使用的EDTA难降解,极难生化处理
本发明采用EDTA-Fe,Na-磷酸活化法制备了EDTA-CBC,并将其负载在HCS上,制备出EDTA-CBC/HCS催化剂。具体的,选用乙二胺四乙酸铁钠(EDTA-Fe,Na)作为改性剂,用于改性CBC,制得EDTA-CBC,再将EDTA-CBC与HCS混合后,加入粘合剂后煅烧,即得铜渣臭氧催化剂。将本发明制得的铜渣臭氧催化剂主要利用化学吸附用于臭氧处理废水中总氰、铜和锌,对废水中总氰的去除率最高可达98.71%,同时,废水中残留的铜和锌的浓度分别为0.448mg/L、0.032 mg/L。
Smart Images

Figure CN118976499B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst preparation technology, and in particular to a copper slag ozone catalyst, its preparation method, and its application. Background Technology
[0002] Cyanide, as a versatile complexing particle, possesses extremely strong complexing ability. (CN) - Once inside the human body, it reacts with stomach acid to form highly toxic hydrogen cyanide. Hydrogen cyanide then reacts with Fe in bodily fluids and oxidases. 3+ When combined, cyanide forms a very stable complex with iron, causing oxygen deficiency in human organs. At the same time, cyanide can also generate thiocyanate compounds in the human body, causing chronic poisoning.
[0003] Currently, treatment methods for cyanide-containing wastewater include homogeneous and heterogeneous methods. Homogeneous methods include oxidation and complexation, while heterogeneous methods include ozone oxidation, activated carbon-oxygen heterogeneous catalytic oxidation, liquid membrane oxidation, and ion exchange. Hydrogen peroxide oxidation is suitable for treating low-concentration cyanide-containing wastewater due to its fast reaction rate; however, the hydrogen peroxide and metal ion catalysts used are expensive, resulting in high treatment costs and the presence of copper ion catalysts that are difficult to recover. In complexation treatment of cyanide-containing wastewater, the generated iron blue precipitate cannot be completely filtered out, leading to insufficient treatment depth, high residual cyanide content, and failure to meet national emission standards. Ozone oxidation does not introduce secondary pollution during the treatment process, but ozone utilization is low, resulting in insufficient treatment depth. Furthermore, ozone catalytic reactions have a certain selectivity, exhibiting poor decomposition ability for certain substances; therefore, to enhance treatment efficiency, catalytic ozonation catalysts are often used.
[0004] In the prior art, CN106396205A discloses a method for removing heavy metals from high-concentration cyanide wastewater. This method involves electrolyzing the high-concentration cyanide wastewater under alkaline conditions using direct current, adding hydrogen peroxide to accelerate the reaction, electrolyzing to obtain low-concentration cyanide wastewater, adjusting the pH of the low-concentration cyanide wastewater to 10-11, adding EDTA and a catalyst for reaction, adding hydrogen peroxide again for deep cyanide removal, and finally using a ferrite method to remove heavy metals from the solution. While this patent utilizes hydrogen peroxide and EDTA to improve electrolysis efficiency, the EDTA used is difficult to degrade and extremely difficult to treat biochemically. Furthermore, EDTA is not easily directly fixed onto the surface of activated carbon.
[0005] Therefore, an ozone catalyst is needed for ozone treatment of cyanide wastewater to improve the selectivity of ozone and thus enhance the degradation effect on cyanide and heavy metal ions in the wastewater. Summary of the Invention
[0006] To address the aforementioned limitations of existing technologies, the present invention aims to provide a copper slag ozone catalyst. This invention utilizes an EDTA-Fe,Na-phosphoric acid activation method to prepare EDTA-CBC, which is then loaded onto modified copper slag to prepare the EDTA-CBC / HCS copper slag ozone catalyst. Specifically, EDTA-Fe,Na ferric sodium ethylenediaminetetraacetate (EDTA-Fe,Na) is selected as a modifier to modify CBC, yielding EDTA-CBC. EDTA-CBC is then mixed with HCS, a binder is added, and the mixture is calcined to obtain the copper slag ozone catalyst. When the copper slag ozone catalyst prepared by this invention is used for ozone treatment of total cyanide, copper, and zinc in wastewater, the removal rate of total cyanide in the wastewater can reach up to 98.71%, while the residual concentrations of copper and zinc in the wastewater are 0.448 and 0.032 mg / L, respectively.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a copper slag ozone catalyst, wherein the copper slag ozone catalyst is prepared from a support and an active component, wherein the support is modified copper slag (HCS) and the active component is EDTA-modified coconut shell ash (EDTA-CBC); the mass ratio of the support to the active component is (0.5-3):1.
[0008] Preferably, the modified copper slag (HCS) is prepared by the following method: copper slag particles are washed, dried and then calcined to obtain modified copper slag; the calcination temperature is 700-750℃ and the calcination time is 4-4.5h.
[0009] Preferably, the particle size of the copper slag particles is 150-200 mesh.
[0010] Preferably, the washing operation is as follows: the copper slag particles are rinsed with deionized water for 10-15 minutes with stirring, and the operation is repeated 2-3 times.
[0011] Preferably, the drying temperature is 105-120℃ and the drying time is 10-12h.
[0012] Preferably, the calcination temperature is 700-750℃, the calcination time is 4-4.5h, and the heating rate during calcination is 10℃ / min. More preferably, the calcination temperature is 722℃ and the calcination time is 4.32h.
[0013] Preferably, the EDTA-modified coconut shell ash is prepared by the following method: coconut shell ash (CBC) and sodium iron ethylenediaminetetraacetate (EDTA-Fe,Na) are mixed and then immersed in a phosphoric acid solution to obtain a sample. The sample is then activated in an inert gas and cooled to room temperature to obtain EDTA-modified coconut shell ash (EDTA-CBC).
[0014] Preferably, the ratio of coconut shell ash to sodium iron ethylenediaminetetraacetate is 1 g: (1-5) mmol.
[0015] A further preferred embodiment is that the ratio of coconut shell ash to sodium iron ethylenediaminetetraacetate is 1 g: 3 mmol.
[0016] Preferably, the concentration of the phosphoric acid solution is 85 wt%.
[0017] Preferably, the mass ratio of coconut shell ash to phosphoric acid solution is 1:3.
[0018] Preferably, the soaking time is 8-12 hours, and more preferably, the soaking time is 10 hours.
[0019] Preferably, N2 is selected as the inert gas.
[0020] Preferably, the activation temperature is 300-800℃, the activation time is 1-6h, and the heating rate is controlled at 10℃ / min during the activation process; more preferably, the activation temperature is 600℃ and the activation time is 2h.
[0021] A second aspect of the present invention provides a method for preparing a copper slag ozone catalyst, comprising the following steps: Modified copper slag, EDTA-CBC and binder are mixed and then added to water to obtain a binder. The binder is calcined, ground and sieved to obtain the copper slag ozone catalyst (EDTA-CBC / HCS).
[0022] Preferably, the mass ratio of EDTA-CBC to modified copper slag is 1:(0.5-3).
[0023] Preferably, the total mass ratio of modified copper slag and EDTA-CBC to the binder is 100:1.
[0024] Preferably, the total mass ratio of modified copper slag, EDTA-CBC and binder to water is 1:1.
[0025] Preferably, the adhesive is hydroxypropyl methylcellulose (HPMC).
[0026] Preferably, the calcination of the binder is performed by placing the binder in a N2 atmosphere and calcining it at 500-600°C for 1.5-2.5 hours.
[0027] Preferably, it is ground through a 100-mesh sieve.
[0028] In a third aspect, the present invention provides an application of a copper slag ozone catalyst in the catalytic ozone treatment of cyanide and heavy metal ions in wastewater.
[0029] Preferably, the heavy metal ions are copper ions and / or zinc ions.
[0030] The beneficial effects of this invention are: This invention utilizes the EDTA-Fe,Na-phosphoric acid activation method to prepare EDTA-CBC, which is then supported on HCS to prepare an EDTA-CBC / HCS catalyst. Specifically, EDTA-Fe,Na iron sodium ethylenediaminetetraacetate (EDTA-Fe,Na) is selected as a modifier to modify CBC, yielding EDTA-CBC. EDTA-CBC is then mixed with HCS, a binder is added, and the mixture is calcined to obtain the copper slag ozone catalyst. The copper slag ozone catalyst prepared by this invention is mainly used for ozone treatment of total cyanide, copper, and zinc in wastewater through chemical adsorption. The removal rate of total cyanide in wastewater can reach up to 98.71%, while the residual concentrations of copper and zinc in the wastewater are 0.448 mg / L and 0.032 mg / L, respectively.
[0031] This invention prepares EDTA-CBC by mixing EDTA and CBC and then activating them by impregnation in a phosphoric acid solution. During the preparation process, the optimal activation temperature is maintained at 600℃ and the optimal activation time at 2 hours. At these temperatures and durations, complete decomposition of EDTA-Fe and Na is ensured. The functional groups generated during the decomposition of EDTA-Fe and Na are beneficial for heavy metal capture, and the active sites are fully exposed, thus improving the catalytic effect. This invention uses the EDTA-Fe,Na-phosphoric acid activation method to prepare EDTA-CBC, effectively avoiding the problem of difficult degradation of EDTA and improving the catalytic effect of the final copper slag ozone catalyst.
[0032] In addition, the present invention modifies copper slag, making the modified copper slag magnetic, easy to recycle and highly efficient in reuse. The modified copper slag generates more reactive oxygen species with higher oxidizing power through hydroxylation in aqueous solution and combination with ozone and oxygen vacancies, thereby improving catalytic efficiency. At the same time, it can also reduce the cost of ozone catalysts and improve ozone utilization, ultimately reducing water treatment costs and promoting the resource utilization of bulk solid waste. Attached Figure Description
[0033] Figure 1 (a) Effect of EDTA-Fe and Na addition on total cyanide removal rate; (b) Effect of EDTA-Fe and Na addition on copper and zinc removal rates. Figure 2 (a) Effect of activation temperature on total cyanide removal rate; (b) Effect of activation temperature on copper and iron removal rate; Figure 3 (a) Effect of activation time on total cyanide removal rate; (b) Effect of activation time on copper and zinc removal rates; Figure 4(a) Effect of EDTA-CBC loading on total cyanide removal rate; (b) Effect of EDTA-CBC loading on copper and zinc removal rates; Figure 5 SEM images of EDTA-CBC and EDTA-CBC / HCS; Figure 6 (a) N2 adsorption-desorption isotherm of the copper slag ozone catalyst EDTA-CBC / HCS prepared in Example 2; (b) pore size distribution diagram. Figure 7 XRD patterns of CBC, HCS, EDTA-CBC, and EDTA-CBC / HCS obtained in Example 2; Figure 8 FT-IR spectra of CBC, phosphoric acid-activated CBC, and EDTA-CBC prepared in Example 2; Figure 9 (a) Effect of ozone concentration on total cyanide removal rate; (b) Effect of ozone concentration on copper and zinc removal rate.
[0034] Figure 10 (a) The effect of the concentration of copper slag ozone catalyst on the total cyanide removal rate in wastewater; (b) The effect of the concentration of copper slag ozone catalyst on the copper and zinc removal rates in wastewater; Figure 11 (a) Effect of initial solution pH on total cyanide removal rate; (b) Effect of initial solution pH on copper and zinc removal rates; Relationship between pH change (c) and O3 concentration in solution (d); Figure 12 (a) Effect of reaction temperature on total cyanide removal rate in wastewater; (b) Effect of reaction temperature on copper and zinc removal rates in wastewater; (c) Relationship between pH change and O3 concentration in solution; (d) Kinetic fitting curves of catalytic ozonation at different temperatures; Figure 13 (a) The effect of the number of cycles on the total cyanide removal rate in wastewater; (b) The effect of the number of cycles on the copper and zinc removal rates in wastewater. Detailed Implementation
[0035] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0036] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0037] Compared with homogeneous catalysts, heterogeneous catalysts have advantages such as simple manufacturing process, low cost, high catalytic activity, good mass transfer effect, and easy reusability. Ozone oxidation, as a heterogeneous catalytic oxidation technology, has been widely used, but it suffers from low ozone utilization. Catalysts are needed to improve ozone utilization. Currently, industrially, catalysts supported on a low-content metal active phase are widely used, priced at 8,000-15,000 yuan / ton, but the amount of active raw material components used is not high.
[0038] Copper slag, a byproduct of pyrometallurgical copper production, has exceeded 16 million tons in my country, with over 50 million tons stockpiled. This low utilization rate has led to resource waste and environmental hazards. However, copper slag's main components are magnetite and bauxite, containing approximately 30-40% iron. This high iron content makes it a high-value secondary resource.
[0039] Based on this, the present invention provides a copper slag ozone catalyst, which is prepared from a support and an active component. The support is modified copper slag (HCS), and the active component is EDTA-modified coconut shell ash (EDTA-CBC). HCS has a large number of metal active sites for catalytic ozonation, while EDTA-CBC has a large specific surface area and abundant functional groups for capturing pollutants. The final removal of pollutants such as cyanide is the result of the synergistic effect of the two. By controlling the mass ratio of EDTA-CBC to HCS, the present invention enables the prepared copper slag ozone catalyst to both catalyze the ozonation degradation of cyanide and effectively adsorb and remove heavy metal ions.
[0040] This invention modifies copper slag, making it magnetic, easily recyclable, and highly reusable. The modified copper slag undergoes electron transfer through hydroxylation in aqueous solution, combining with ozone and utilizing oxygen vacancies to generate more reactive oxygen species with higher oxidizing power, thus improving catalytic efficiency. Simultaneously, it reduces the cost of ozone catalysts, increases ozone utilization, and ultimately lowers water treatment costs and facilitates the resource recovery of bulk solid waste. The mechanism of ozone decomposition and oxidation catalyzed by modified copper slag mainly involves two aspects: When the solution pH is lower than the zero isoelectric point of the copper slag catalyst, metal ions on the copper slag surface combine with water to form a hydroxylation interface. Ozone and hydroxyl groups on the copper slag surface form a five-membered ring structure through coordination bonds and hydrogen bonds, transferring electrons. This electron transfer disrupts the stable conjugated structure, causing ozone molecules to decompose and generate a series of reactive oxygen species, including ·OH and superoxide radicals (•O). - 2) Secondly, small molecule organic matter passes through the Fe on the surface of copper slag. 3+ Complexation reduces Fe 3+ / Fe 2+ The redox potential promotes the reaction of ·OH and ·O. - The generation of 2 increases the reaction rate.
[0041] The EDTA-CBC / HCS prepared in this invention primarily exhibits chemisorption for cyanide, copper, and zinc. The EDTA-CBC / HCS catalytic O3 oxidation system follows the free radical law, with the reactive species •OH and •O participating in the reaction. - 2 and 1 O2, and the process is accompanied by an increase in the valence state of Fe, a decrease in adsorbed and bound oxygen, and a transformation of unsaturated functional groups to saturated forms. The removal of cyanide is a result of both direct and indirect oxidation by O3.
[0042] The main components of the copper slag used in this invention are shown in the table below. The experimental materials used in the embodiments of this invention are all conventional experimental materials in the art and can be purchased through commercial channels.
[0043] The wastewater was obtained by diluting the original wastewater from the roasting process at a gold leaching plant in Yantai by 20 times. The total cyanide concentration in the diluted water sample was approximately 72 mg / L, and the ion concentrations of Cu and Zn were 244 mg / L and 168 mg / L, respectively. The coconut shell charcoal was purchased from Guangdong Xuanyu Charcoal Industry Co., Ltd.
[0044] Example 1: Optimization of preparation conditions for copper slag ozone catalyst EDTA-CBC / HCS By adjusting the preparation parameters in the copper slag ozone catalyst preparation process, and based on the impact of the prepared copper slag ozone catalyst on the removal rates of total cyanide, copper, and zinc, the optimal experimental parameters were selected. The specific experimental steps for the copper slag ozone catalyst to catalyze the ozone treatment of total cyanide, copper, and zinc in wastewater are as follows: The copper slag ozone catalyst and wastewater were placed in a reaction tower. After ozone was introduced, the reaction proceeded, and 30 mL samples were taken every 5 minutes. The samples were then filtered through a 0.45 μm filter membrane after N2 was introduced to remove residual O3, and the concentrations of cyanide, copper, and zinc in the water were measured. The experiment was repeated three times, and the average value was used to calculate the removal rate.
[0045] The formula for calculating the removal rate (RE) is as follows: , In the formula, C t C and C0 are the concentrations (mg / L) of the target substance (cyano, copper, or zinc) in the solution at time t and the initial time, respectively.
[0046] 1. Amount of EDTA-Fe and Na added Five treatment groups were set up in this experiment. The addition amounts of EDTA-Fe and Na in each treatment group were 1 mmol / g, 2 mmol / g, 3 mmol / g, 4 mmol / g, and 5 mmol / g, respectively. In the preparation of copper slag ozone catalysts in each treatment group, the mass ratio of EDTA-CBC to HCS was 2:1, the activation temperature was 600℃, and the activation time was 2 h.
[0047] A control group was also set up, in which no EDTA-Fe,Na was added during the preparation of the copper slag ozone catalyst. The removal rates of total cyanide, copper, and zinc in wastewater by the copper slag ozone catalysts prepared in each treatment group and the control group were investigated. The results are as follows: Figure 1 As shown.
[0048] During the experiment, C O3 =30mg / L, O3 gas flow rate is 0.2L / min, copper slag ozone catalyst dosage is 0.4g / L, reaction temperature is 20℃, and reaction time is 30min.
[0049] Depend on Figure 1 As shown in (a), the total cyanide removal rate of the component without EDTA-Fe,Na was 87.24%. At addition levels of 2 mmol / g and 3 mmol / g, it exhibited better catalytic effect and a faster degradation rate, with total cyanide removal rates of 91.51% and 93.88%, respectively. With further increases in the addition amount, the degradation efficiency of total cyanide remained almost unchanged, and even slightly decreased. Figure 1 (b) It can be seen that with the increase of EDTA-Fe and Na addition, the removal rates of Zn and Cu are improved, especially Zn, which is almost completely removed. The EDTA-Fe and Na modification effect shows a more significant improvement in heavy metal removal compared to catalytic oxidation of cyanide.
[0050] 2. Activation temperature This experiment included six treatment groups, with activation temperatures of 300℃, 400℃, 500℃, 600℃, 700℃, and 800℃, respectively. In the preparation of the copper slag ozone catalyst, the mass ratio of EDTA-CBC to HCS was 2:1, the concentration of EDTA-Fe,Na added was 3 mmol / g, and the activation time was 2 h.
[0051] The removal rates of total cyanide, copper, and zinc in wastewater by the copper slag ozone catalysts prepared in each treatment group were investigated, and the results are as follows: Figure 2 As shown. During the experiment, C O3 =30mg / L, O3 gas flow rate is 0.2L / min, copper slag ozone catalyst dosage is 0.4g / L, reaction temperature is 20℃, and reaction time is 30min.
[0052] Depend on Figure 2 (a) It can be seen that as the activation temperature increases from 300℃ to 800℃, the cyanide removal rate increases from 85.53% to 97.37%. When the activation temperature is above 600℃, the degradation effect increases slowly. Figure 2 (b) It can be seen that the removal efficiency of Cu and Zn gradually increases as the activation temperature increases from 300℃ to 600℃. Considering the removal rates of total cyanide and metal ions, 600℃ is determined to be the optimal activation temperature.
[0053] 3. Activation time Six treatment groups were set up in this experiment, with activation times of 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h, respectively. In the preparation of copper slag ozone catalyst, the mass ratio of EDTA-CBC to HCS was 2:1, the concentration of EDTA-Fe,Na was 3 mmol / g, and the activation temperature was 600℃.
[0054] The removal rates of total cyanide, copper, and zinc in wastewater by the copper slag ozone catalysts prepared in each treatment group were investigated, and the results are as follows: Figure 3 As shown. During the experiment, C O3 =30mg / L, O3 gas flow rate is 0.2L / min, copper slag ozone catalyst dosage is 0.4g / L, reaction temperature is 20℃, and reaction time is 30min.
[0055] Depend on Figure 3 (a) It can be seen that after a reaction of 30 min, the activation time has little effect on the removal of total cyanide. Figure 3 (b) It can be seen that after 1 h, when EDTA-Fe and Na are sufficiently activated, the activation time has little effect on the final removal efficiency of Cu and Zn. Therefore, the optimal activation time is determined to be 2 h.
[0056] 4. Load capacity of EDTA-CBC Five treatment groups were set up in this experiment. In each treatment group, the mass ratio of EDTA-CBC to HCS was 3:1, 2:1, 1:1, 1:2, and 1:3, respectively. The activation temperature for each treatment group in the preparation of copper slag ozone catalyst was 600℃ and the activation time was 2h.
[0057] The removal rates of total cyanide, copper, and zinc in wastewater by the copper slag ozone catalysts prepared in each treatment group were investigated, and the results are as follows: Figure 4 As shown. During the experiment, C O3 =30mg / L, O3 gas flow rate is 0.2L / min, copper slag ozone catalyst dosage is 0.4g / L, reaction temperature is 20℃, and reaction time is 30min.
[0058] Depend on Figure 4(a) It can be seen that the system can achieve the maximum catalytic efficiency when the mass ratio of EDTA-CBC to HCS is 1:2, at which point the degradation rate of cyanide is 97.37%, and the remaining concentrations of Cu and Zn are 0.034 mg / L and 0.524 mg / L, respectively. The preparation conditions of the catalyst should be determined by comprehensively considering various factors. Therefore, the mass ratio of EDTA-CBC to HCS in subsequent experiments was determined to be 1:2.
[0059] In summary, based on the removal rates of total cyanide, copper, and zinc, production costs, and energy considerations, the final preparation conditions for the copper slag ozone catalyst were determined as follows: EDTA-Fe, Na dosage 2 mmol / g, activation temperature and time 600℃ and 2h, respectively, and the mass ratio of EDTA-CBC to HCS 1:2. The prepared copper slag ozone catalyst was labeled as EDTACBC / HCS.
[0060] Example 2: Preparation method of copper slag ozone catalyst (1) Mix coconut shell ash CBC and sodium iron ethylenediaminetetraacetate at a ratio of 1g:2mmol, then immerse the mixture in an 85wt% phosphoric acid solution for 10h to obtain a sample. The mass ratio of coconut shell ash to phosphoric acid solution is 1:3. Place the sample in a N2 atmosphere and heat it to 600℃ at a rate of 10℃ / min. Activate the sample at this temperature for 2h and then cool it to room temperature to obtain EDTA-CBC. (2) 150-mesh copper slag particles were screened out, and the particles were rinsed with deionized water for 15 min. After repeated washing 3 times, the particles were dried at 120℃ for 12 h. The copper slag particles were then placed in an air atmosphere and heated to 722℃ at a rate of 10℃ / min. The particles were then calcined at this temperature for 4.32 h to obtain modified copper slag (HCS). (3) After mixing modified copper slag and EDTA-CBC at a mass ratio of 2:1, hydroxypropyl methylcellulose (HPMC) is added as a binder and mixed evenly. The mixture is then added to water to obtain a binder. The total mass ratio of modified copper slag, EDTA-CBC and binder to water is 1:1. The binder is placed in a N2 atmosphere and calcined at 550°C for 2 hours. After grinding through a 100-mesh sieve, copper slag ozone catalyst (EDTA-CBC / HCS) is obtained.
[0061] The morphology of the copper slag ozone catalyst (EDTA-CBC / HCS) prepared in this embodiment was analyzed, such as... Figures 5-8 As shown.
[0062] Depend on Figure 5It can be seen that many aggregates grow on the surface of the activated EDTA-CBC. The composite material EDTA-CBC / HCS exhibits the characteristics of a rough EDTA-CBC surface covered with aggregates, and also shows the characteristics of the elongated crystal structure of HCS minerals, proving that the composite catalyst was successfully prepared. According to surface elemental analysis, the CBC activated by EDTA-Fe, Na and phosphoric acid impregnation is uniformly covered with P, Fe, Na and other elements, indicating that the activation process successfully improved the surface structure of CBC, but the Fe content is relatively low. After loading EDTA-CBC onto HCS, the C and P elements mainly contributed by EDTA-CBC are uniformly distributed on the catalyst surface, the Fe content increases significantly, and Si, which is characteristic of HCS, appears, further proving that the composite of EDTA-CBC and HCS is effective.
[0063] Depend on Figure 6 As can be seen, according to the isotherm types defined by IUPAC, the N2 adsorption-desorption curve of the copper slag ozone catalyst is Type I. This indicates that the surface structure of the copper slag ozone catalyst mainly exhibits EDTA-CBC characteristics. Furthermore, the presence of the H3-type hysteresis loop suggests that the material is primarily a non-rigid aggregate of layered particles, mostly composed of slit-type channels. The pore size distribution of the copper slag ozone catalyst is mainly concentrated below 50 nm, indicating that it is a predominantly mesoporous material.
[0064] Depend on Figure 7 It can be seen that by comparing and analyzing the components and crystal characteristics of the active substances generated during the reaction process with the standard card, the crystal characteristics of EDTA-CBC are similar to those of C and Fe2P4O. 12 According to the standard card matching, under the action of phosphoric acid, EDTA-Fe,Na converts Fe into Fe2P4O. 12 It grows in situ on the surface of CBC. EDTA-CBC / HCS possesses both Fe3O4 and Fe2P4O4 properties. 12 The crystal characteristics indicate that the composite material EDTA-CBC / HCS was successfully prepared.
[0065] Depend on Figure 8 It can be seen that at a wavelength of 3420 cm -1 The absorption peak at 1570 cm⁻¹ is attributed to the stretching vibration of OH. -1 The absorption peak at 1260 cm⁻¹ is mainly attributed to the stretching vibration of aromatic C=C molecules. -1 1050 cm -1 and 710 cm -1 The absorption peaks at 510 cm⁻¹ correspond to the CN bending vibration, C=O bond, and CH bond in the amide III band, respectively. -1This is due to the OPO structure, indicating a strong interaction between phosphoric acid and the biochar surface during activation. Comparing phosphoric acid-activated CBC and EDTA-CBC, the peaks for OH, C=C, C=O, CN, and CH are significantly enhanced, indicating that in-situ activation of CBC not only alters physical properties such as pore structure but also changes its microscopic chemical morphology. EDTA-Fe and Na decompose at high temperatures, and amino and carboxyl groups grow on the CBC surface, increasing the unsaturation of the biochar and the number of N and O functional groups, which is beneficial for the adsorption reaction.
[0066] Experimental Example 1: The copper slag ozone catalyst prepared in Example 2 was used to remove total cyanide, copper and zinc from the wastewater by ozone treatment, and the experimental conditions were optimized. The specific experimental steps were the same as in Example 1.
[0067] 1. Ozone dosage concentration This experiment included five treatment groups with ozone (O3) concentrations of 15 mg / L, 20 mg / L, 25 mg / L, 30 mg / L, and 35 mg / L, respectively. The O3 concentration was calculated as the ozone dosage (mg) divided by the wastewater volume (L). The removal rates of total cyanide, copper, and zinc in each treatment group were investigated, and the results are shown below. Figure 9 As shown in the figure. During the experiment, the O3 gas flow rate was 0.2 L / min, the mass ratio of copper slag ozone catalyst EDTA-CBC / HCS to wastewater was 0.4 g: 1 L, the reaction temperature was 20 ℃, and the reaction time was 30 min.
[0068] like Figure 9 As shown in (a), the removal rate of total cyanide gradually increases with increasing O3 concentration. When the O3 concentration exceeds 25 mg / L, the increase in the removal rate of total cyanide is not significant, but the removal rate accelerates significantly. At this point, the content of oxidant in the system is not the decisive factor limiting the reaction. When the O3 concentration is 25 mg / L, the removal rate of total cyanide is 97.07%. Figure 9 (b) It can be seen that the O3 dosage significantly reduces Cu, while lower O3 concentrations achieve good Zn removal. Considering both experimental results and economic factors, a O3 dosage of 25 mg / L yields relatively good removal results for both Cu and Zn, with residual concentrations of 0.539 and 0.041 mg / L, respectively. Therefore, the optimal ozone dosage is 25 mg / L.
[0069] 2. Dosage concentration of copper slag ozone catalyst This experiment included seven treatment groups. The dosage concentrations of the copper slag ozone catalyst in each group were 0 g / L, 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, and 0.6 g / L, respectively. The concentration of the copper slag ozone catalyst was calculated as: dosage of copper slag ozone catalyst (g) / volume of wastewater (L). The removal rates of total cyanide, copper, and zinc in each treatment group were investigated, and the results are as follows: Figure 10 As shown in the figure. During the experiment, the concentration of O3 added was 25 mg / L, the flow rate of O3 gas was 0.2 L / min, the reaction temperature was 20℃, and the reaction time was 30 min.
[0070] Depend on Figure 10 (a) It can be seen that after 30 min of reaction, the total cyanide removal rate in the component without catalyst was 75.19%, and the removal rate gradually increased after catalyst addition. When the EDTA-CBC / HCS dosage was 0.3 g / L, the total cyanide removal rate reached the critical value of 94.96%. Figure 10 (b) It can be seen that the copper slag ozone catalyst has a significant effect on the removal of Cu and Zn. The residual concentrations of Cu and Zn in the component without catalyst are 1.121 and 0.096 mg / L, respectively. With the increase of the amount of copper slag ozone catalyst EDTA-CBC / HCS added, the residual concentrations of Cu and Zn in the component gradually decrease.
[0071] 3. Initial pH of the solution This experiment included six treatment groups with initial solution pH values of 8.0, 8.5, 9.0, 9.5, 10.0, and 10.5, respectively. The removal rates of total cyanide, copper, and zinc in each treatment group were investigated, and the results are as follows: Figure 11 As shown in the figure. During the experiment, the concentration of O3 added was 25 mg / L, the flow rate of O3 gas was 0.2 L / min, the mass ratio of copper slag ozone catalyst EDTA-CBC / HCS to wastewater was 0.4 g: 1 L, the reaction temperature was 20 ℃, and the reaction time was 30 min.
[0072] Depend on Figure 11 (a) It can be seen that in the standalone ozonation system, the removal rate of total cyanide first increases and then decreases with increasing pH, reaching its optimal level of 86.81% at pH 9.5. Figure 11 (b) It can be seen that, comparing the ozonation system and the catalytic ozonation system, the addition of a catalyst significantly enhances the removal of metal ions, especially Cu. Increasing pH does not significantly promote ion precipitation. pH 9.5 is the optimal value for the synergistic removal of Cu and Zn, at which point their residual concentrations are 0.44 and 0.03 mg / L, respectively. Figure 11 (c) and Figure 11 (d) It can be seen that when the pH is between 8 and 8.5, the O3 and OH groups in both systems... - The consumption of cyanide and OH groups was similar, but the catalytic oxidation system showed better cyanide removal than the ozonation system alone. This indicates that the indirect oxidation performance of the free radicals generated by the catalytic reaction is higher than that of direct oxidation. At pH 9-9.5, the catalytic oxidation system produced O3 and OH groups... - The consumption of the catalyst is significantly higher than that of a standalone ozonation system. At this point, the catalytic activity of the catalyst is significantly enhanced, and indirect oxidation dominates. Both direct and indirect oxidation are inhibited at pH above 10. Considering the removal of total cyanide, Cu, and Zn, as well as the utilization of O3, the catalytic performance is best and most economical at pH 9.5.
[0073] 4. Reaction temperature This experiment included three treatment groups, with reaction temperatures of 20℃, 30℃, and 40℃. The removal rates of total cyanide, copper, and mixed zinc were investigated in each treatment group. The results are as follows: Figure 12 As shown in the figure. During the experiment, the concentration of O3 added was 25 mg / L, the flow rate of O3 gas was 0.2 L / min, the mass ratio of copper slag ozone catalyst EDTA-CBC / HCS to wastewater was 0.3 g: 1 L, the initial pH of the solution was 9.5, and the reaction time was 30 min.
[0074] Depend on Figure 12 As can be seen from (a) and (c), the removal rate of total cyanide decreases slightly with increasing temperature, and the reaction rate constant also decreases. This indicates that the negative impact of decreased O3 solubility outweighs the promoting effect of increased temperature on the reaction. Figure 12 (b) It can be seen that the removal of C is concentrated in the first 15-20 minutes, while the removal of Zn is mainly concentrated in the first 5 minutes of the reaction. Figure 12 (c) It can be seen that the amount of O3 dissolved in the system decreases with increasing temperature, indicating that the dissolution of O3 is greatly affected by temperature. Furthermore, at low temperatures, OH... - The consumption is relatively large. Based on comprehensive analysis, the optimal reaction temperature is 20℃.
[0075] In summary, the copper slag ozone catalyst EDTA-CBC / HCS prepared in Example 2 was used for ozone treatment of total cyanide, copper, and zinc in wastewater. The feed-to-liquid ratio of ozone to wastewater was 25 mg:1 L, the feed-to-liquid ratio of copper slag ozone catalyst to wastewater was 0.3 g:1 L, the initial pH of the solution was 9.5, and the reaction temperature was 20 °C.
[0076] Experimental Example 2: The copper slag ozone catalyst prepared in Example 2 was investigated for its effect on the removal of total cyanide, copper, and zinc from wastewater through ozone treatment. The catalyst was recycled five times, and the removal efficiency of total cyanide, copper, and zinc was used as the evaluation index. The results are as follows: Figure 13As shown.
[0077] Depend on Figure 13 It can be seen that the initial ozonation catalytic oxidation of the catalyst achieved a total cyanide removal rate of 98.71%, which decreased by 6.45% after 5 cycles. The residual concentrations of Cu and Zn in the initial catalyst system were 0.448 and 0.032 mg / L, respectively. After 5 cycles, the residual concentrations of Cu and Zn in the system were 0.568 and 0.062 mg / L, respectively.
[0078] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A copper slag ozone catalyst, characterized in that, The copper slag ozone catalyst is prepared from a support and an active component. The support is modified copper slag, and the active component is EDTA-modified coconut shell ash. The mass ratio of the support to the active component is (0.5-3):
1. The modified copper slag is prepared by the following method: copper slag particles are washed, dried and then calcined to obtain modified copper slag; the calcination temperature is 700-750℃ and the calcination time is 4-4.5h. The EDTA-modified coconut shell ash is prepared by the following method: coconut shell ash and sodium ferric ethylenediaminetetraacetate are mixed and then immersed in phosphoric acid solution to obtain a sample. The sample is then activated in an inert gas and cooled to room temperature to obtain EDTA-modified coconut shell ash. The material-to-liquid ratio of coconut shell ash to sodium ferric ethylenediaminetetraacetate is 1 g: (1-5) mmol, the immersion time is 8-12 h, the activation temperature is 300-800 ℃, the activation time is 1-6 h, the inert gas is N2, and the mass ratio of coconut shell ash to phosphoric acid solution is 1:
3.
2. The copper slag ozone catalyst as described in claim 1, characterized in that, The copper slag particles have a particle size of 150-200 mesh, and the drying temperature is 105-120℃ with a drying time of 10-12h.
3. The method for preparing the copper slag ozone catalyst according to claim 1 or 2, characterized in that, Includes the following steps: Modified copper slag, EDTA-modified coconut shell ash, and binder are mixed and then added to water to obtain a binder. The binder is calcined, ground, and sieved to obtain the copper slag ozone catalyst.
4. The preparation method according to claim 3, characterized in that, The binder is hydroxypropyl methylcellulose, and the mass ratio of the total mass of modified copper slag, EDTA-modified coconut shell ash and binder to water is 1:1; the mass ratio of the total mass of modified copper slag, EDTA-modified coconut shell ash and binder to binder is 100:
1.
5. The preparation method according to claim 4, characterized in that, The procedure for calcining the binder is as follows: place the binder in a N2 atmosphere and calcine it at 500-600℃ for 1.5-2.5 hours.
6. The application of the copper slag ozone catalyst according to claim 1 or 2 in the catalytic ozone treatment of cyanide and heavy metal ions in wastewater.
7. The application as described in claim 6, characterized in that, The heavy metal ions are copper ions and / or zinc ions.
Citation Information
Patent Citations
Method for removing heavy metal by carrying out cyanide breaking on high-concentration cyanide wastewater
CN106396205A
Method for preparing ozone catalytic oxidation catalyst for treating cyanide waste water
CN102008965A
Transition metal catalyst applied to ozone catalytic advanced oxidation sewage treatment and preparation method thereof, and ozone catalytic advanced oxidation sewage treatment method
CN106964353A